Integrated Care: A Pill for All Ills? - Maria Goddard; Anne R. Mason (Kerman University of Medical Sciences, 2017)
There is an increasing policy emphasis on the integration of care, both within the healthcare sector and also between the health and social care sectors, with the simple aim of ensuring that individuals get the right care, in the right place, at the right time. However, implementing this simple aim is rather more complex. In this editorial, we seek to make sense of this complexity and ask: what does integrated care mean in practice? What are the mechanisms by which it is expected to achieve its aim? And what is the nature of the evidence base around the outcomes delivered?